The improved prognosis of FLT3-internal tandem duplication but not tyrosine kinase domain mutations in acute myeloid leukemia in the era of targeted therapy: a real-world study using large-scale electronic health record data - Matthew Schwede; Gladys Rodriguez; Vanessa E. Kennedy; Solomon Henry; Douglas Wood; Gabriel N. Mannis; Ravindra Majeti; Jonathan H. Chen; Eran Bendavid; Tian Yi Zhang (Haematologica)
Not available.